2023
DOI: 10.1039/d2ra07897j
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence and stability of Tb doped CaF2 nanoparticles

Abstract: Luminescence properties of CaF2:Tb3+ nanoparticles were studied in order to investigate the effect of CaF2 native defects on the photoluminescence dynamics of Tb3+ ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…S13 (ESI †) shows the CIE representation of the solvatochromic effect for compound 6a using Colour Calculator software. 25 We observed that 6a demonstrated strong emission intensity in a nonpolar solvent like toluene as compared to an aprotic polar solvent like DMSO and exhibited a good fluorescence quantum yield of 30% in toluene. On moving from non-polar to polar solvents, a remarkable red-shift (bathochromic shift) was observed in its fluorescence spectra showing the ICT characteristics of compound 6a.…”
Section: Photophysical Studiesmentioning
confidence: 74%
“…S13 (ESI †) shows the CIE representation of the solvatochromic effect for compound 6a using Colour Calculator software. 25 We observed that 6a demonstrated strong emission intensity in a nonpolar solvent like toluene as compared to an aprotic polar solvent like DMSO and exhibited a good fluorescence quantum yield of 30% in toluene. On moving from non-polar to polar solvents, a remarkable red-shift (bathochromic shift) was observed in its fluorescence spectra showing the ICT characteristics of compound 6a.…”
Section: Photophysical Studiesmentioning
confidence: 74%
“…Moreover, the pure emission color with color coordinates of the irradiated and nonirradiated forms was further quantified by CIE chromaticity diagram (inset in Figure 1e,f). 46 The other three materials (BPI-I, NEt-BDPI, and BDPI-2Y) did not show any photochromic response like BDPI (Figure S14). Similar to their unique absorption profiles, the solid-state emission profiles of these four 1,4-bis(imidazolyl)benzene derivatives are completely distinguishable (Figure 2b).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…In solid-state emission spectra, a hypsochromic shift of 45 nm was observed for BDPI-II with respect to BDPI-I , which could be the effect of the presence of different solvent molecules that influences the stacking of chromophores in the crystal lattice (Figure a). , A similar fluorescence quenching was observed in the case of BDPI-II ′ in comparison with BDPI-II , which suggests the analogous effect of light on both BDPI-I and BDPI - II forms (Figure f). Moreover, the pure emission color with color coordinates of the irradiated and nonirradiated forms was further quantified by CIE chromaticity diagram (inset in Figure e,f) …”
Section: Resultsmentioning
confidence: 99%
“…The color purity of the ideal concentration of 15 mol% of Tb 3+ , by assessing the color coordinates ( x,y ), which were calculated on the basis of each emission spectra, MgLa 2 V 2 O 9 manufactured phosphors may be measured. From Figure 19, the CIE 1931 chromaticity coordinates diagram is shown, where x = 0.321 and y = 0.533 show the enhanced luminescence intensity and color purity [27]. Thus, the prepared phosphor could be used as a potential candidate for novel luminescent materials toward the display of green light emitting applications.…”
Section: Resultsmentioning
confidence: 99%
“…From Figure 10, it shows the CIE 1931 chromaticity coordinates diagram where x = 0.51 and y = 0.336 showing the enhanced luminescence intensity and color purity [27]. Thus, the prepared phosphor could be suggested as a potential candidate for novel luminescent materials toward the display of red-light emitting applications.…”
Section: Energy Level Schemementioning
confidence: 99%